2007
DOI: 10.4049/jimmunol.179.8.5204
|View full text |Cite
|
Sign up to set email alerts
|

PDL1 Is Required for Peripheral Transplantation Tolerance and Protection from Chronic Allograft Rejection

Abstract: The PD-1:PDL pathway plays an important role in regulating alloimmune responses but its role in transplantation tolerance is unknown. We investigated the role of PD-1:PDL costimulatory pathway in peripheral and a well established model of central transplantation tolerance. Early as well as delayed blockade of PDL1 but not PDL2 abrogated tolerance induced by CTLA4Ig in a fully MHC-mismatched cardiac allograft model. Accelerated rejection was associated with a significant increase in the frequency of IFN-γ-produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
157
3
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 186 publications
(170 citation statements)
references
References 56 publications
8
157
3
2
Order By: Relevance
“…Interestingly, the number of infiltrating T cells with regulatory characteristics (CD4-and Foxp3 positivity) significantly increased in tumor tissues of our analyzed cancer patients from early to advanced tumor stages. This data are in accordance with the observation that a blockade of PD-L1 led to a decreased number of regulatory T cells [37]. Regulatory T cells can also suppress the function of cytotoxic CD8-positive T cells, thus inhibiting anti-tumor immune responses, largely through a mechanism that requires cell-cell contact.…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, the number of infiltrating T cells with regulatory characteristics (CD4-and Foxp3 positivity) significantly increased in tumor tissues of our analyzed cancer patients from early to advanced tumor stages. This data are in accordance with the observation that a blockade of PD-L1 led to a decreased number of regulatory T cells [37]. Regulatory T cells can also suppress the function of cytotoxic CD8-positive T cells, thus inhibiting anti-tumor immune responses, largely through a mechanism that requires cell-cell contact.…”
Section: Discussionsupporting
confidence: 79%
“…The results of studies using B7-H1-deficient mice or treatment with anti-B7-H1 or anti-PD-1 mAb have suggested that tissueassociated B7-H1 is involved in the PD-1-mediated regulatory pathway in autoimmunity and allotransplantation (7)(8)(9)(12)(13)(14). However, the separate contributions of tissue and lymphoid B7-H1 were not clearly discriminated in these studies.…”
mentioning
confidence: 62%
“…Alefacept treatment led to an increased amount of PDL1 expressing APCs (CD19 ϩ B cells) and CD4 ϩ T cells compared with activated but untreated cells. PDL1 negatively regulates T cell activation, promotes T cell apoptosis and has been reported to play an important role in transplantation tolerance (23)(24)(25)(26)(27)(28). How Alefacept induces PDL1 expression on B cells needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…These gene markers were selected for the following reasons: CD3 as a control to follow potential changes in T cell composition at transcriptional level, CD69 as Haider et al (15) showed that nonresponders express higher transcription levels of CD69 in pretreatment PBMCs, Foxp3 to indirectly study changes in regulatory T cell frequencies, PD-L1 to asses differences in gene expression of negatively regulating costimulatory molecules (23)(24)(25)(26)(27)(28), and TOAG-1 (Acc. No: BE115945) and RHAMM as they have been recently described to be differentially expressed in the periphery during induction and maintenance of immunological tolerance in allogeneic kidney graft recipients (29).…”
Section: Discussionmentioning
confidence: 99%